Research in social movements, conflicts and change. Vol. 31 - Coy, Patrick G. (Bingley, U.K. : Emerald, 2010)
This latest volume in the Research in Social Movements, Conflicts and Change series contains three sections of data-driven articles that address topics central to scholarship on social movements and conflict resolution. Section One contains two papers on the Palestinian-Israeli conflict, one focused on the Arab Israeli Land Day campaign and its implications for political process theory, while the other analyzes the emotional landscape of the long-running Women in Black vigils. Section Two contains four papers linked by their treatment of tactical and strategic issues associated with gender-based and gay and lesbian social movements, organizations, and their campaigns and activities. The two articles in Section Three treat themes associated with the complex intersection of identity formation and mobilization. As has long been the RSMCC series tradition, Volume 31 showcases top-level, original, and multi-method research on a variety of movements, organizations and conflicts in ways that contribute to theory-building.
Introduction / Patrick G. Coy -- Emotion maps of participation in protest : the case of women in black against the occupation in Israel / Tova Benski -- Learning from failures : why and how 'scale shift' failed to launch : evidence from the case of the Israeli-Arab land day / Eitan Y. Alimi, Liora Norwich -- The pitfalls of winning : a comparison of two first-wave feminist organizations / Alison Faupel -- Implicit politics in a free and open space : belly dance, leisure activity, and gender identity / Dennis J. Downey, Sandrine Zerbib and Derek Christopher Martin -- Dominant tactics in social movement tactical repertoires : anti-gay ballot measures, 1974-2008 / Amy L. Stone -- Mobilizing in the shadow of the law : lesbian and gay rights in the aftermath of Bowers v. Hardwick / Steven A. Boutcher -- Freedom summer abroad : biographical pathways and cosmopolitanism among international human rights workers / Matthew P. Eddy -- The making of organic indigenous-campesino intellectuals : catechist training in the diocese of San Cristóbal and the roots of the Zapatista uprising / Christopher Gunderson -- All the news that's fit to print? Silence and voice in mainstream and ethnic press accounts of African American protest / Melissa F. Weiner.
Print version record
Keywords: Political Science -- General; Political Science -- Peace; Sociology; Political science & theory; Social movements; Social conflict; Social change